Clinicopathological Profile of Patient with Solitary Thyroid Nodule Presented to OPD at a Tertiary Care Hospital Pakistan - Azmat Ali Khan, Bakht Babar, Jamal Ahmad Khan, Sana, Zakirullah Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the clinicopathological profile of patient with solitary thyroid nodule presented to opd at a tertiary care hospital Pakistan Study Design: Cross sectional study Settings: Department of Diabetes and endocrinology, Hayatabad Medical Complex, Peshawar Materials & Methods: Patients with confirmed diagnosis of a solitary thyroid nodule through imaging or clinical examination were included. Patients with a history of thyroidectomy or thyroid cancer, those with multiple thyroid nodules were excluded. Results: The mean age of the patients in the study was 48.7 years (SD = 2.11). In terms of gender, 42.4% were female, while 57.6% were male. Swelling with dysphagia was reported by 25.6% of patients, swelling with pain by 20.8%, and swelling with fever by 1.6%. The distribution of thyroid nodule location revealed that 50.4% were in the left lobe, 48% in the right lobe, and a small percentage (1.6%) were bilateral. The ultrasonography findings of the patients revealed diverse characteristics of thyroid nodules. The most common were hypoechoic nodules, present in 38.4% of cases. Isoechoic nodules were observed in 26.4%, while mixed echogenicity was noted in 17.6% of patients. A smaller proportion, 9.6%, exhibited thyroid nodules with cystic components. A significant proportion, 57.6%, yielded benign results, while 22.4% were categorized as suspicious. Practical Implication: Understanding the clinicopathological profile of patients with solitary thyroid nodules presenting at a tertiary care hospital in Pakistan can aid in refining diagnostic and treatment strategies, ultimately improving patient outcomes and reducing unnecessary interventions. Conclusion: In conclusion, our study on the clinicopathological profile of patients with solitary thyroid nodules at a tertiary care hospital reveals a diverse presentation of clinical and ultrasonographic features. Keywords: Solitary thyroid nodule, Clinicopathological profile, Ultrasonography, Fine-Needle Aspiration, Thyroid Disorders